MiR-200b Inhibits Tumor Growth and Chemoresistance via Targeting p70S6K1 in Lung Cancer - Jin, Hui-Fang; Wang, Ju-Feng; Song, Ting-Ting; Zhang, Jun; Wang, Lin (Frontiers in Oncology, 2020)
Downregulation of microRNA-200b (miR-200b) has been identified in a range of cancers, yet the specific mechanisms whereby it influences lung cancer growth require further exploration. We determined that lung cancer patient tumor samples exhibit decreased miR-200b expression, and we further found this miRNA to inhibit tumor growth via interfering with ERK1/2 and AKT signaling, targeting p70S6K1 to suppress HIF-1α expression. This miRNA further rendered H1299 cells more sensitive to cisplatin while impairing their proliferative and invasive potential through its ability to target and inhibit the activity of p70S6K1. These results were further confirmed in a murine xenograft model in which miR-200b also inhibited the growth of tumor and suppressed p70S6K1, p-AKT, p-ERK1/2, and HIF-1α expression. These findings clearly demonstrate a role for miR-200b in suppressing lung cancer development, making it a potentially relevant target for future diagnostic and therapeutic interventions.